1996
DOI: 10.1101/gad.10.15.1966
|View full text |Cite
|
Sign up to set email alerts
|

Zygotic degradation of two maternal Cdc25 mRNAs terminates Drosophila's early cell cycle program.

Abstract: In Drosophila embryos the maternal/zygotic transition (MZT) in cell cycle control normally follows mitosis 13. Here we show that this transition requires degradation of two maternal mRNAs, string and twine, which encode Cdc25 phosphatases. Although twine is essential for meiosis and string is essential for most mitotic cycles, the two genes have mutually complementing, overlapping functions in the female germ line and the early embryo. Deletion of both gene products from the female germ line arrests germ-line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
167
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(176 citation statements)
references
References 55 publications
8
167
1
Order By: Relevance
“…Early Drosophila embryos express 2 homologs of Cdc25, String and Twine. 16 Recent studies in Drosophila have shown that onset of the MBT is due to rapid degradation of the Cdc25 ortholog Twine at the precise time the MBT begins, with the half-life of Twine changing from 20 min to 5 min (Fig. 2).…”
Section: The Midblastula Transition: Introducing Cell Cycle Complexitmentioning
confidence: 99%
“…Early Drosophila embryos express 2 homologs of Cdc25, String and Twine. 16 Recent studies in Drosophila have shown that onset of the MBT is due to rapid degradation of the Cdc25 ortholog Twine at the precise time the MBT begins, with the half-life of Twine changing from 20 min to 5 min (Fig. 2).…”
Section: The Midblastula Transition: Introducing Cell Cycle Complexitmentioning
confidence: 99%
“…In contrast, our observations are consistent with a gradual decay of maternally provided cdc25a message throughout gastrulation followed by dynamic spatially restricted expression upon completion of gastrulation. The drop in Cdc25 activity at the Drosophila MZT is required for a long G2 phase during cellularization of the embryo (Edgar and Datar, 1996), and is followed by pulses of string transcription that drive mitosis in domains corresponding to cell fate assignments. In zebrafish, only three mitotic domains have been described (Kane et al, 1992), and we see correlation between cdc25a expression and these domains.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Drosophila have established the importance of Cdc25 in coordinating cell proliferation with developmental events. Early synctial cell cycles are driven by maternally provided mRNA and protein from the Drosophila cdc25 homolog, string (Edgar and Datar, 1996). After the maternal-zygotic transition (MZT, cycle 10), maternal string mRNA is degraded (Edgar and Datar, 1996) and spatio-temporally patterned zygotic string expression begins (Edgar and O'Farrell, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include the Drosophila orthologue of the mammalian c-myc transcription factor and oncogene, dMyc, which drives growth and progression through G1 to S-phase (Johnston et al 1999), the essential G1 to S-phase Cyclin complex, Cyclin E (CycE) and its Cyclin-dependent-kinase (Cdk) partner Cdk2, which triggers S-phase by promoting DNA replication (Knoblich et al 1994;Neufeld et al 1998;Richardson et al 1995), and the Drosophila orthologue of the Cdc25 phosphatase, String (Stg), which is required for G2/M progression and promotes mitotic entry by activating the Cdk1/Cyclin B complex (Edgar and Datar 1996). CycE and Stg are the rate limiting factors for S-phase and mitosis, respectively, and both are activated by the Drosophila orthologue of human E2F1 protein, dE2F1 (Neufeld et al 1998).…”
Section: Linking the Ecdysone Pulse To Cell Cyclementioning
confidence: 99%